Macromol. Mater. Eng. 2/2017. Issue 2 (February 2017) - Lee, Gyeong Won; Lee, Seunghyun; Kim, Jang Hwan; Yim, Sang‐Gu; Ryu, Jooyeon; Lee, Eunji; Lee, Jaebeom; Yoo, Seong Il; Yang, Seung Yun
Abstract : Front Cover: A new approach to prepare free‐standing biodegradable nanopillar arrays on flexible substrates is developed by using plasma etching with block copolymer micelles encapsulating Au nanoparticles as an etching mask. This method can offer a feasible route to create vertically‐aligned nanostructures of various materials with dimensional controllability. This is reported by Gyeong Won Lee, Seunghyun Lee, Jang Hwan Kim, Sang‐Gu Yim, Jooyeon Ryu, Eunji Lee, Jaebeom Lee, Seong Il Yoo, and Seung Yun Yang in article number 1600361.